ANALYSIS OF THE MAIN INDICATORS OF THE INSURANCE COMPANY’S FINANCIAL STABILITY USING SIMULATION MODELLING - Клепікова, О. А.; Поліщук, С. О.; Сарамков, О. А.; Нечай, Д. В. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2019)
The purpose of insurance is to accumulate funds to fulfill obligations to its clients, as well as to invest further in the expansion of insurance activities and the development of the country’s economy. The success of insurance companies depends to a large extent on their financial status, that is, financial stability and solvency. The financial condition of an insurance company is characterized by the indicators that describe its ability to develop and successfully operate in a competitive market environment. The stable financial condition of the insurer is a guarantee of development in the conditions of the market economy and an insurance of the stability of the development of the insurance market in the country. The purpose of this research is to assess the financial stability of a non-life insurance company and to analyze the main factors affecting it with the use of computer simulation modelling. The simulation model covers the main processes of the non-life insurance company and is based on the application of financial analysis methods, economic and mathematical methods, and modern simulation technologies. Based on the simulation model, the financial stability of the insurance company is assessed, namely the analysis of the insurance company’s profitability, income, expenses, indicators of profitability; the coefficients of financial stability of the insurance fund and the level of insurance reserves for the analysis of the adequacy of the insurance fund are calculated; the actual and normative solvency margin is calculated for controlling the fulfillment of solvency conditions; the solvency ratio (autonomy) is calculated; the equity ratio is calculated and an analysis of the adequacy of equity is carried out. The developed simulation model can be used to increase the level of planning and analytical reporting, to improve methods of conducting insurance operations, to plan and forecast the activity, and to increase the validity of managerial decisions.